Lost to Follow-Up: Complications of an Invasive Giant Prolactinoma - Blackmon, Melodie M (Cureus, 2020)
Invasive giant prolactinomas are a rare type of prolactin-secreting tumors. Most lactotroph adenomas, including giant prolactinomas, consist of the sparsely granulated subtype and respond well to medical therapy with dopamine agonists. Proptosis due to intra-orbital tumor extension and ischemic infarction are two rare complications associated with these tumors. We report a case of a 51-year-old woman with a 30-year history of a macroprolactinoma who was lost to follow-up and returned with severe proptosis, a 10-cm invasive sellar mass on imaging, and markedly elevated serum prolactin levels, consistent with invasive giant prolactinoma. She was initially managed with dopamine agonists followed by palliative debulking of the tumor, which microscopically demonstrated a highly proliferative neoplasm predominantly consisting of sparsely granulated lactotroph adenoma with a minor component of the rare and aggressive acidophil stem cell adenoma subtype. Postoperatively, she developed a large left middle cerebral artery infarct and ultimately died. This case is notable in that it demonstrates the aggressive nature of invasive giant prolactinomas when not treated and highlights two rare findings in patients with this tumor: orbital invasion and ischemic infarct.